Strategi Kuliah Sambil Bekerja Oleh Mahasiswa (Studi Kasus: Mahasiswa Bekerja di Universitas Negeri Padang) - Arif Rahman Hakim; Mira Hasti Hasmira (Naradidik: Journal of Education and Pedagogy, 2022)
This research is motivated by the number of students who study while working but can finish their studies on time, based on this, this study aims to determine the strategies of students who work in completing their studies. The purpose of this study is in line with the analytical theory for the case of "Lecture Strategy while working by Padang State University students". The method used is a qualitative approach with the type of case study and the informant selection technique is a purposive sampling technique with a total of 12 informants. Data was collected by means of observation, interviews, documentation with data analysis techniques from Miles and Huberman. The results of the study show how the strategies of students studying while working at Padang State University are: (1) Focusing on goals such as determining priorities and optimizing time, (2) Communication at work, (3) Maintaining college grades, (4) Maintaining rest patterns.